2019
DOI: 10.1021/acs.jafc.9b04563
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Midgut Cadherin from Two Moths in Different Bacillus thuringiensis Action Mechanisms: Correlation among Toxin Binding, Cellular Toxicity, and Synergism

Abstract: The midgut cadherin has been described as one of the main functional receptors for Bacillus thuringiensis (Bt) toxins. Plutella xylostella (P. xylostella) and Helicoverpa armigera (H. armigera) are two major target pests of Bt toxins in China, and the roles of their cadherins in the action of Bt toxins have been only partially studied. Here, we expressed the two cadherins in Sf9 cells and their partial extracellular domains in Escherichia coli and tested them for Bt toxin binding, cellular toxicity, and synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The CmCad protein showed typical topology for Cry receptor cadherins in Lepidoptera (Chen et al, 2009; Fabrick et al, 2009;Flannagan et al, 2005;Park and Kim, 2013), consisting of 11 extracellular CRs and transmembrane and CYTs. Sequential analysis of CmCad-derived peptides localized the Cry TBR to the CmCad-CR9-11 (T1211-L1456) region, which is homologous to the Cry1Ac TBR previously described in cadherins from H. armigera and P. xylostella (Gao et al, 2019). Interestingly, the CmCad-CR9-11 peptide displayed highaffinity binding by both Cry1Ac and Cry2Aa, suggesting that a shared binding site exists in this region.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The CmCad protein showed typical topology for Cry receptor cadherins in Lepidoptera (Chen et al, 2009; Fabrick et al, 2009;Flannagan et al, 2005;Park and Kim, 2013), consisting of 11 extracellular CRs and transmembrane and CYTs. Sequential analysis of CmCad-derived peptides localized the Cry TBR to the CmCad-CR9-11 (T1211-L1456) region, which is homologous to the Cry1Ac TBR previously described in cadherins from H. armigera and P. xylostella (Gao et al, 2019). Interestingly, the CmCad-CR9-11 peptide displayed highaffinity binding by both Cry1Ac and Cry2Aa, suggesting that a shared binding site exists in this region.…”
Section: Discussionmentioning
confidence: 72%
“…Lyophilized activated Cry1Ac, Cry1B, Cry1C, Cry1F and Cry2Aa toxins were purchased from Envirotest-China (an agent of Envirologix Inc., Portland, ME, USA), and solubilized in sodium carbonate buffer (pH 9.6), aliquoted and stored at À80 C until used. Soluble Cry toxins were biotinylated with the EZ-Link Sulfo-NHS-SS-Biotinylation kit (Thermo Fisher Scientific) as described before (Gao et al, 2019). Briefly, 28.4 μl of 10 mM biotin was used to label 1 mg Cry toxin in a 1 ml final volume reaction.…”
Section: Insects and Bt Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A susceptible strain of P. xylostella (HN) was purchased from Keyun and has been maintained in the laboratory without exposure to insecticides or Bt toxins for more than 5 years (Gao et al, 2019). Larvae of P. xylostella were reared on an artificial diet based on wheat germ powder at 27 ± 1°C with a 14:10 (L:D) photoperiod.…”
Section: Insects Strain and Rearingmentioning
confidence: 99%
“…For instance, it has been reported that the cadherin from Plutella xylostella (PxCad) is not associated with resistance in P. xylostella to Cry1Ac [17]. However, other reports suggest that PxCad is a functional receptor of Cry1Ac, since PxCad can increase cytotoxicity of Cry1Ac when expressed in the Sf9 cell line [18][19][20]. In addition, we reported that Spodoptera litura cadherin (SlCad), in contrast to HaCad, cannot increase cytotoxicity of Cry1Ac when expressed in Hi5 cells, suggesting that SlCad is not a functional receptor of Cry1Ac in S. litura [14].…”
Section: Introductionmentioning
confidence: 99%